Peanut Oil Cake: A Novel Substrate for Enhanced Cell Growth and Prodigiosin Production from Serratia marcescens CF-53 - Naik, Chandrashekhar; JM, Srisevita; KN, Shushma; Noorin, Farah; AC, Shilpa; CD, Muttanna; N, Darshan; D, Sannadurgappa (Journal of Research in Biology, 2012)
Different agro-wastes such as peanut oil cake (POC), coconut oil cake (COC), sesame oil cake (SOC), safflower seed oil cake (SFOC) and cotton seed oil cake (CSOC) were screened for prodigiosin production through fermentation employing Serratia marcescens-CF-53. POC was highly beneficial for the pigment production. Fermentation parameters have been standardized; maximum amount of pigment was obtained ( 40 mg ml-1) in POC extract at 30oC for 42 h using 8% inoculum density (1X107cell/ml) compared to PG broth (14.2 mg ml-1). The pigment yield was almost three fold higher than that of the PG broth. Use of POC extract as a raw material for pigment production could be of great commercial significance. This report appears to be the first one on prodigiosin production using POC as a substrate.